A Relational Understanding of Co-Educating and Learning: Information Sharing and Advice Seeking Behavior in a Dairy Cooperative in Gujarat, India. Issue 2 (December 2021) - Singh, Shyam; Holvoet, Nathalie; Dewachter, Sara
Highlights: Co-education and learning are an essential principle of the ICA's statement on Cooperative Identity. Social embeddedness and social capital play a crucial role in promoting knowledge sharing and learning behaviour among cooperative members. Knowledge-based and position-based hierarchies play prominent roles in information sharing and advice sharing. Just being the leader in the collective does not earn members' trust. Members seek help or collaborate with leaders who have the required knowledge and skills to solve their issues. Abstract: This article, building on the 5 th principle of the Statement of the Cooperative Identity explores the practice of co-educating and learning behavior among the members of a dairy cooperative society. The study adopts a social network approach by focusing on two relational social ties: information sharing and advice-seeking . Building on a case of a 55-year-old dairy cooperative in India, the social network analysis finds information-sharing relations among members to be inclusive, with no members isolated, and information exchanged along formal and knowledge hierarchies. Likewise, information sharing is horizontal, with information smoothly exchanged even among new and already established members, as is the transfer of leadership roles from the older members of the cooperatives to the younger members. Advice-seeking networks tend to be a bit more centralized toward board members and members exerting day-to-day leadership because of their knowledge and expertise regarding the organization and its policies. Our analysis suggests inclusive information sharing among members and a well-structured and functioning advice and knowledge-sharing network that contributes to learning of the cooperative members.